Surface and interfacial properties of Fe-C-O-Cr alloys in contact with alumina - Novák V.; Řeháčková L.; Váňová P.; Smetana B.; Konečná K.; Drozdová Ľ.; Rosypalová S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, temperature and concentration dependencies on density and surface tension of liquid Fe-C-O-Cr alloys (1.93 - 4.80 wt.% Cr) were investigated in high-temperature resistance observation furnace by a sessile drop method during heating from liquidus temperature to 1600°C. The interfacial characteristics (interfacial tension, wetting angle, work of adhesion, and spreading coefficient) of liquid alloy/alumina system were also determined depending on temperature. The effect of temperature and chromium content on surface and interfacial properties was proven in case of all examined alloys. Based on the fact that the content of surface-active elements such as oxygen (up to 195 ppm) and sulfur (up to 545 ppm) was higher, the influence of activities of both mentioned elements on surface tension of alloy samples was assessed. Particular attention was paid to the dependence of the surface tension temperature coefficient on oxygen and sulfur activity.